Effect of the Period of Glucocorticoid Administration on Bone Quality in Patients with Autoimmune Inflammatory Rheumatism Disease (AIIRD) - Werdiningsih, Yulyani; Sunarso, indrayana; Nurudhin, Arief (Indonesian Basic and Experimental Health Sciences, 2025)
Introduction Inflammatory autoimmune rheumatic disease (AIIRD) such as rheumatoid arthritis, systemic lupus erythematosus, and Sjogren's syndrome often requires long-term glucocorticoid therapy. Despite its effectiveness, glucocorticoids are recognized to cause decreased bone quality and increase the risk of osteoporosis. This study aims to evaluate the effect of the period of glucocorticoid administration on bone quality parameters in AIIRD patients. Methods This study was an observational analytical study with a cross-sectional design. A total of 28 female patients with AIIRD were divided into two groups based on the period of glucocorticoid administration: less than 24 months and more than 24 months. The parameters to be measured included bone mineral density (BMD), Collagen Type I C-Telopeptide (CTX), Vitamin D3 levels, and Calcium Ions. Data analysis was conducted using the Mann-Whitney test and the unpaired t-test with a significance level of p<0.05. Results There was no statistically significant difference between the two groups on all measured parameters. The mean BMD in the group of less than 24 months was 0.9471 kg/m², while in the group of more than 24 months it was 0.8920 kg/m² (p>0.05). The mean CTX also did not differ significantly between the two groups (0.2474 vs. 0.2508 ng/mL; p>0.05). Vitamin D3 and Calcium Ion levels showed similar results in the absence of significant differences (Vitamin D3: 15,596 vs. 16,255 ng/mL; Calcium Ion: 1,075 vs. 1,040 mmol/L; p>0.05). Conclusions The period of glucocorticoid administration does not show a significant effect on bone quality in AIIRD patients in this study. Nonetheless, regular monitoring and an individualized approach are still necessary to prevent bone complications in patients receiving long-term glucocorticoid therapy.